Location, Location, Location: The Impact of Migratory Heterogeneity on T Cell Function - Baaten, Bas J.; Cooper, Andrea M.; Swain, Susan L.; Bradley, Linda M. (Frontiers in Immunology, 2013)
T cell migration is crucial for an effective adaptive immune response to invading pathogens. Naive and memory T cells encounter pathogen antigens, become activated and differentiate into effector cells in secondary lymphoid tissues, and then migrate to the site(s) of infection where they exert effector activities that control and eliminate pathogens. To achieve activation, efficient effector function, and good memory formation, T cells must traffic between lymphoid and non-lymphoid tissues within the body. This complex process is facilitated by chemokine receptors, selectins, CD44, and integrins that mediate the interactions of T cells with the environment. The expression patterns of these migration receptors (MR) dictate the tissues into which the effector T cells migrate and enable them to occupy specific niches within the tissue. While MR have been considered primarily to facilitate cell movement, we highlight how the heterogeneity of signaling through these receptors influences the function and fate of T cells in situ. We explore what drives MR expression heterogeneity, how this affects migration, and how this impacts T cell effector function and memory formation.